2022
DOI: 10.3390/agriculture13010039
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Microencapsulated Probiotics on Performance, Organ Development, Diarrhoea Incidences, Blood Parameters, Intestinal Histomorphology and Microflora in Weaning Piglets

Abstract: The study aimed to assess the effects of the dietary supplementation of microencapsulated L. acidophilus and L. plantarum and their combination on the growth performance, organ development, diarrhoea incidences, blood profiles, intestinal histomorphology and microflora in weaned piglets. For that, 160 piglets with an average body weight (BW) of 8.52 ± 0.15 kg were divided into four groups (40 piglets/group) and allotted to one of the four dietary treatments as follows: a basal diet (C diet) or a basal diet con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…This effect is beneficial for chickens’ immunity because E. coli is able to multiply in large numbers in the host body and cause peritonitis, salpingitis, and pneumonitis, while under optimal breeding conditions marked by appropriate temperature, humidity, ventilation, and fecal management, the occurrence of colibacillosis is effectively prevented ( 13 ). Previous studies have evaluated the antioxidant activity of various Lactobacillus strains and indicated that LS showed good antioxidative properties ( 6 , 65 ), alleviating possible detrimental effects in the monogastric gut. In the present study, CSD15 with LS supplementation elevated the beneficial bacteria such as Lactobacilli in the ceca and excreta.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This effect is beneficial for chickens’ immunity because E. coli is able to multiply in large numbers in the host body and cause peritonitis, salpingitis, and pneumonitis, while under optimal breeding conditions marked by appropriate temperature, humidity, ventilation, and fecal management, the occurrence of colibacillosis is effectively prevented ( 13 ). Previous studies have evaluated the antioxidant activity of various Lactobacillus strains and indicated that LS showed good antioxidative properties ( 6 , 65 ), alleviating possible detrimental effects in the monogastric gut. In the present study, CSD15 with LS supplementation elevated the beneficial bacteria such as Lactobacilli in the ceca and excreta.…”
Section: Discussionmentioning
confidence: 99%
“…Health problems in broilers often arise due to their rapid growth rates, leading to issues like leg disorders and cardiovascular problems (3), underscoring the need for holistic approaches to improve bird wellbeing. The incorporation of feed additives and probiotics plays a vital role in addressing these concerns by promoting gut health, enhancing nutrient absorption, and bolstering immune responses, ultimately improving broiler welfare and productivity (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…Probiotics can increase the efficiency of nitrogen utilization, improve nitrogen utilization, and increase BUN concentrations in pigs [32,33]. On the other hand, other studies have demonstrated that supplementation of probiotics has no effect on blood profiles of growing pigs [24,34]. These results were probably due to feed intake time or amount and gender differences.…”
Section: A C C E P T E Dmentioning
confidence: 96%
“…Similarly, Batista et al [4], after supplementing immunomodulatory feed additives in weaned Nellore calves, found that their treatment had no effect on animal performance. Likewise, in Lefter et al study [5] on weaning piglets, probiotics supplements showed potential in enhancing production performance.…”
mentioning
confidence: 96%
“…Consequently, the anticipated advantages of employing the immunomodulatory feed additive might have been addressed. The impact of microencapsulated Lactobacillus acidophilus and Lactobacillus plantarum supplementation, individually and in combination, was studied by Lefter et al [5] on weaning piglets. Their findings revealed a remarkable reduction in diarrhea incidence that was particularly evident in the Lactobacillus plantarum and combined Lactobacillus acidophilus + Lactobacillus plantarum groups.…”
mentioning
confidence: 99%